MANAJEMEN SARANA PRASARANA MUTU PEMBELAJARAN DI SMK NEGERI 1 REJANG LEBONG - Murniyanto Murniyanto; Siswanto Siswanto (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2021)
Good management of infrastructure is expected to create favorable conditions for teachers and students to be in school. the management of infrastructure in SMK 1 Curup is already maximal. Strengths: Facilitate the teacher in delivering learning material, facilitate students in understanding the material, facilitate in obtaining educational information, increase students 'interest in reading, develop students' talents, facilitate the implementation of practicum, develop psychomotor training participants in well-available family classes, first-class housing that is always conducive and comfortable, building maintenance one year ago can minimize maintenance costs. Weaknesses: Maintenance of media is less effective, instructions for the use of media are often not requested by students, infrastructure is poorly controlled. Authors' expectations, For the use and maintenance of educational facilities and infrastructure, all school members need to pay attention to the rules and instructions that have been listed for the smooth creation of the learning process and have a sense of responsibility, need infrastructure that can be well maintained and minimize damage.